Ghrelin Increases Beta-Catenin Level through Protein Kinase A Activation and Regulates OPG Expression in Rat Primary Osteoblasts. (17th March 2015) - Mrak, Emanuela; Casati, Lavinia; Pagani, Francesca; Rubinacci, Alessandro; Zarattini, Guido; Sibilia, Valeria
Abstract : Ghrelin, by binding growth hormone secretagogue receptor (GHS-R), promotes osteoblast proliferation but the signaling mechanism of GHS-R on these cells remains unclear. Since canonical Wnt/ β -catenin pathway is critically associated with bone homeostasis, we investigated its involvement in mediating ghrelin effects in osteoblasts and in osteoblast-osteoclast cross talk. Ghrelin (10 −10 M) significantly increased β -catenin levels in rat osteoblasts (rOB). This stimulatory action on β -catenin involves a specific interaction with GHS-R1a, as it is prevented by the selective GHS-R1a antagonist, D-Lys 3 -GHRP-6 (10 −7 M). The effect of ghrelin on β -catenin involves the phosphorylation and inactivation of GSK-3 β via protein kinase A (PKA). Inhibition of PKA activity reduces the facilitatory action of ghrelin on β -catenin stabilization. Ghrelin treatment of rOB significantly increases the expression of osteoprotegerin (OPG), which plays an important role in the regulation of osteoclastogenesis, and this effect is blocked by D-Lys 3 -GHRP-6. Furthermore, ghrelin reduced RANKL/OPG ratio thus contrasting osteoclastogenesis. Accordingly, conditioned media from rOB treated with ghrelin decreased the number of multinucleated TRAcP+ cells as compared with the conditioned media from untreated-control rOB. Our data suggest new roles for ghrelin in modulating bone homeostasis via a specific interaction with GHSR-1a in osteoblasts with subsequent enhancement of both β -catenin levels and OPG expression.